The effectiveness of field trip in the teaching of EOP to business management and ICT students at IIUM: a case study - Yusof Khan , Zarinah Jan; Othman, Khairiah; Adam, Zalika (2014)
Malaysia is currently experiencing an emerging trend to focus on workplace specific language needs. This paper investigates if the field trip activity which is a component in EOP, helps graduates in meeting the industry's language requirement.